Die Reformation Voraussetzungen und Durchsetzung - Mörke, Olaf 1952- (Enzyklopädie deutscher Geschichte, 2017)
"On the occasion of the 500th anniversary of the Protestant Reformation, Olaf Mörke has put together a new edition of his highly praised textbook on one of the most important themes in German history. The volume has been updated while keeping its proven three-part organization into presentation, research, and bibliography. A supplement to the research section and bibliography presents research developments and trends since the previous edition."--Provided by publisher